Variable element enrichment sources and contributions to volcanic rocks along the Lesser Antilles Island Arc - Atlas, Zachary D.; Germa, Aurélie; Boss, Brenna; Meireles, Osvaldo; Ward, Ami; Ryan, Jeffrey G. (Frontiers in Earth Science, 2022)
Understanding relationships between different components involved in subduction-related recycling of sediment at arc volcanic systems has long been a focus of study. It is generally understood that volcanic arc lavas incorporate materials from the down-going slab including fluids, fluid mobile elements (FME), and fluid modified large ion lithophile elements (LILE), largely derived from subducted sediments and serpentinized ultramafic rocks. Past studies have presumed bulk sediment contributions rather than addressing localized variations in sediment composition. We examine trace element variability along the Lesser Antilles Island Arc (LAIA) and show that sediment inputs via fluid transfer to the mantle wedge are necessary to explain high B (up to 50 ppm), high B/La ratios, and higher As, Cs, Rb in the central LAIA. In contrast, the northern portion of LAIA is enriched in Ba, Sr and U/Th, with low FME. Grenada has low FME abundances, low Ba/La, but higher Sm/La. Our results suggest that modification of LAIA mantle source by fluid addition is important for the central islands but find that sediment enrichment is more likely in the northern section of the LAIA. Li/Yb ratios suggest the Grenada signature is chemically more comparable to sediment from DSDP Site 144 (Demerara Rise), while Martinique magmas in the central LAIA are affiliated to sediments from Site 543 (offshore Dominica). Unexpectedly, the northern portion of LAIA is not directly relatable to Site 543 sediments but instead trends back toward a sediment source similar in composition to Site 144 but with lower B, lower La/Sm and higher Ba. Binary mixing models suggest the northern islands are likely influenced by small amounts of sediment melt similar to average Site 144 sediments, but with Ba concentrations ranging from 1250-1500 ppm. Trace element ratios then likely result from different levels of contribution from sediment packages both spatially and temporally along the arc, with some variation evident among samples from the same island. We suggest that the process of recycling subducted sediment along the arc is variable along the length of the LAIA, wherein the trace element relationships are likely strongly influenced by the types of sediment being subducted along strike.